Will Losing Black Physicians Be a Consequence of the COVID-19 Pandemic?. (December 2020) - Filut, Amarette; Carnes, Molly
Abstract : A compelling case exists that increasing the number of Black physicians trained and practicing in the United States is one effective intervention to promote health equity and reduce the persistent health disparities that have become glaringly evident during the COVID-19 pandemic. However, the U.S. physician workforce has relatively few Black physicians. Blacks comprise approximately 13% of the U.S. population but only 5% of practicing physicians. In this Invited Commentary, the authors caution that the COVID-19 pandemic may erode the meager progress that has been made in increasing the number of Black physicians. This loss of Black physicians may happen because Black patients are overrepresented among cases of COVID-19, Black physicians care for relatively more Black patients often in settings with less access to SARS-CoV-2 testing and personal protective equipment, and Black physicians have more comorbid chronic conditions that increase their own susceptibility to mortality from COVID-19. All organizations in which physicians train and practice must redouble their efforts to recruit, train, and retain Black physicians. If nothing else, the COVID-19 pandemic must make academic health centers and health care systems recognize Black physicians as the precious resource they are and protect and reward them accordingly.